The 18 kDa translocator protein (peripheral benzodiazepine receptor) expression in the bone of normal, osteoprotegerin or low calcium diet treated mice. - Winnie Wai-Ying Kam; Steven R Meikle; Hong Zhou; Yu Zheng; Julie M Blair; Marcus Seibel; Colin R Dunstan; Richard B Banati (PLoS ONE, 2012)
The presence of the translocator protein (TSPO), previously named as the mitochondrial or peripheral benzodiazepine receptor, in bone cells was studied in vitro and in situ using RT-qPCR, and receptor autoradiography using the selective TSPO ligand PK11195.In vitro, the TSPO is highly expressed in osteoblastic and osteoclastic cells.In situ, constitutive expression of TSPO is found in bone marrow and trabecular bone, e.g., spongiosa. Mice with a reduction of bone turnover induced by a 4-day treatment of osteoprotegerin reduces [(3)H]PK11195 binding in the spongiosa (320±128 Bq x mg(-1), 499±106 Bq x mg(-1) in saline-treated controls). In contrast, mice with an increase in bone turnover caused by a 4-day low calcium diet increases [(3)H]PK11195 binding in the spongiosa (615±90 Bq x mg(-1)). Further, our study includes technical feasibility data on [(18)F]fluoride microPET imaging of rodent bone with altered turnover. Despite [(18)F]fluoride having high uptake, the in vivo signal differences were small. Using a phantom model, we describe the spillover effect and partial volume loss that affect the quantitative microPET imaging of the small bone structures in experimental mouse models. In summary, we demonstrate the expression of TSPO in small rodent bone tissues, including osteoblasts and osteoclasts. A trend increase in TSPO expression was observed in the spongiosa from low to high bone turnover conditions. However, despite the potential utility of TSPO expression as an in vivo biomarker of bone turnover in experimental rodent models, our small animal PET imaging data using [(18)F]fluoride show that even under the condition of a good biological signal-to-noise ratio and high tracer uptake, the currently achievable instrument sensitivity and spatial resolution is unlikely to be sufficient to detect subtle differences in small structures, such as mouse bone.